Kebijakan Moneter dalam Tinjauan Tiga Mazhab Ekonomi Islam Terhadap Permintaan Uang - Abelia Olivia Putri; Vani Gusti Andini; Suci Hayati (Indo Publishing, 2025)
This study aims to examine monetary policy from the perspective of the three major schools of thought in Islamic economics Mainstream, Alternative, and Revivalist schools with a focus on the concept of money demand. These schools differ significantly in their epistemological foundations, methodologies, and approaches to economic theory and policy within the Islamic framework. This research employs a qualitative-descriptive method through a literature review of various prominent Islamic economic thinkers. The findings reveal that the Mainstream school is adaptive to the modern economic system, accepting conventional monetary instruments adapted to Sharia principles, and interprets money demand through a modified Keynesian approach that excludes speculative motives. In contrast, the Alternative school rejects interest-based monetary systems, emphasizes the role of the real sector, and views money as a tool for productive transactions that must avoid accumulation and speculation. Meanwhile, the Revivalist school takes a normative and idealistic stance, advocating a return to the dinar and dirham (gold and silver currency) system and rejecting fiat money, aiming to establish monetary justice based on intrinsic value. The study concludes that the differences among these schools reflect the rich diversity of thought within Islamic economics. No single school offers a definitive solution to monetary issues, making an integrated approach across schools more contextual and applicable in formulating Islamic monetary policies that are just, stable, and responsive to the challenges of the global economy.